Interaction of smoking and social status on the risk of respiratory outcomes in a Swedish adult population: A Nordic Epilung study - Andersén, Heidi; Kankaanranta, Hannu (Respiratory Medicine, 2023)
Background: Evidence abounds on the independent roles of social class and smoking in relation to obstructive airway diseases, but data are sparse on the impact of their interaction. We evaluated whether and to what extent social class and smoking interact in relation to risk of respiratory diseases in adults. Methods: Data from the population-based studies, West Sweden Asthma Study (WSAS, n = 23,753) and Obstructive Lung Disease in Northern Sweden studies (OLIN, n = 6519), were used, constituting randomly selected adults aged 20–75 years. Bayesian network analysis was used to estimate the probability for the interaction between smoking and socioeconomic status in relation to respiratory outcomes. Results: Occupational and educational SES modified the association between smoking and the probability of allergic and non-allergic asthma. Former smokers who were at intermediate non manual employees and manual workers in service had higher probability of allergic asthma compared to professionals and executives. Furthermore, former smokers with primary education had higher probability of non-allergic asthma than those with secondary and tertiary education. Similarly, former smokers among professionals and executives had higher probability of non-allergic asthma than manual and home workers and primary educated. Likewise, allergic asthma due to former smoking was higher among highly educated compared to low educated. Conclusions: Beyond their independent roles, socioeconomic status and smoking interact in defining the risk of respiratory diseases. Clearer understanding of this interaction can help to identify population subgroups at most need of public health interventions. Peer reviewed